Genome-wide analysis of MADS-box families and their expressions in flower organs development of pineapple (Ananas comosus (L.) Merr.) - Pan, Xiaolu; Ouyang, Yanwei; Wei, Yongzan; Zhang, Bencheng; Wang, Jing; Zhang, Hongna (Frontiers in Plant Science, 2022)
MADS-box genes play crucial roles in plant vegetative and reproductive growth, better development of inflorescences, flower, and fruit. Pineapple is a typical collective fruit, and a comprehensive analysis of the MADS-box gene family in the development of floral organs of pineapple is still lacking. In this study, the whole-genome survey and expression profiling of the MADS-box family in pineapple were introduced. Forty-four AcMADS genes were identified in pineapple, 39 of them were located on 18 chromosomes and five genes were distributed in five scaffolds. Twenty-two AcMADS genes were defined as 15 pairs of segmental duplication events. Most members of the type II subfamily of AcMADS genes had higher expression levels in floral organs compared with type I subfamily, thereby suggesting that AcMADS of type II may play more crucial roles in the development of floral organs of pineapple. Six AcMADS genes have significant tissue-specificity expression, thereby suggesting that they may participate in the formation of one or more floral organs. This study provides valuable insights into the role of MADS-box gene family in the floral organ development of pineapple.